Step-by-step explanation:
1. (2+4+1)/9 = 7/9
2. 2 1/3 + 2/3 = 2 + (1+2)/3 = 2 + 3/3 = 2+1 = 3
3. 1 1/5 + 2 3/5 = 1+2 + 1/5 + 3/5 = 3 + (1+3)/5 =
3 4/5
4. 5/6 + 2/10 + 1/5 = 5/6 + 1/5 + 1/5 = 5/6 + 2/5
= (5×5)/(6×5) + (2×6)/(5×6)
= 25/30 + 12/30
= (25+12)/30
= 37/30 = 1 7/30
5. 3 1/2 + 4 2/3
= 3+4 + 1/2 + 2/3
= 7 + (1×3)/(2×3) + (2×2)/(3×2)
= 7 + 3/6 + 4/6
= 7 + (3+4)/6 = 7 7/6 = 8 1/6
6. 9/13 - 5/13 = (9-5)/13 = 4/13
7. 7 6/8 - 5 2/8
= (7-5) + (6/8 - 2/8)
= 2 + 4/8
= 2 1/2
8. 2/3 - 3/7
= (2×7)/(3×7) - (3×3)/(7×3)
= 14/21 - 9/21 = (14-9)/21 = 5/21
9. 11 1/5 - 5 4/5
= 10 6/5 - 5 4/5
= (10-5) + (6/5 - 4/5)
= 5 + 2/5 = 5 2/5
10. 15 4/5 - 7 7/10
= (15-7) + (4/5 - 7/10)
= 8 + (4×2)/(5×2) - 7/10
= 8 + 8/10 - 7/10
= 8 + 1/10
= 8 1/10
<h2>3</h2>
Step-by-step explanation:
The equation of line passing through the two points is ![\frac{y-y_{1} }{x-x_{1} }=\frac{y_{2} -y_{1}}{x_{2} -x_{1}}](https://tex.z-dn.net/?f=%5Cfrac%7By-y_%7B1%7D%20%7D%7Bx-x_%7B1%7D%20%7D%3D%5Cfrac%7By_%7B2%7D%20-y_%7B1%7D%7D%7Bx_%7B2%7D%20-x_%7B1%7D%7D)
When substituted,the equation becomes ![\frac{y-6}{x-2}=\frac{18-6}{6-2}](https://tex.z-dn.net/?f=%5Cfrac%7By-6%7D%7Bx-2%7D%3D%5Cfrac%7B18-6%7D%7B6-2%7D)
which when simplified is ![y=3\times x](https://tex.z-dn.net/?f=y%3D3%5Ctimes%20x)
The line clearly passes through origin.
The distance between two points is ![\sqrt{(y_{1}-y_{2} )^{2}+(x_{1}- x_{2} )^{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%28y_%7B1%7D-y_%7B2%7D%20%29%5E%7B2%7D%2B%28x_%7B1%7D-%20x_%7B2%7D%20%29%5E%7B2%7D%7D)
Distance between origin and
is
.
Distance between origin and
is ![\sqrt{360}](https://tex.z-dn.net/?f=%5Csqrt%7B360%7D)
Scale factor is ![\frac{distance\text{ }of\text{ }p_{2}\text{ from origin}}{distance \text{ } of \text{ } p_{1}\text{ from origin}}](https://tex.z-dn.net/?f=%5Cfrac%7Bdistance%5Ctext%7B%20%7Dof%5Ctext%7B%20%7Dp_%7B2%7D%5Ctext%7B%20from%20origin%7D%7D%7Bdistance%20%5Ctext%7B%20%7D%20of%20%5Ctext%7B%20%7D%20p_%7B1%7D%5Ctext%7B%20from%20origin%7D%7D)
So,scale factor is ![\frac{\sqrt{360} }{\sqrt{40} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B360%7D%20%7D%7B%5Csqrt%7B40%7D%20%7D)
which when simplified becomes 3.
A)
It looks like the [irregular] hexagon has 3 rectangles and 2 triangles within it.
So let's exclude the triangular corners on bottom left and top right for now.
First we have a large rectangle covering most of the upper left of the polygon. 20 ft × 7 ft = 140 sq.ft.
Now we have a rectangle on the bottom right. The width is 11 ft, so take the 7 away from that, 4 ft. × 14 ft. on bottom. 4 ft × 14 ft = 56 sq.ft.
The last small rectangle fits on the right between the 2 other rectangles. It is 24-20 on top/bottom × 7-6 right/left. 4 ft × 1 ft = 4 sq.ft.
Now for the triangles: bottom left is 11-7 × 24-14 = 4 ft × 10 ft. 1/2bh = 1/2×10×4 = 20 sq.ft.
Top right is 24-20 × 11-5 = 4 ft × 6 ft. 1/2bh = 1/2×4×6 = 12 sq.ft.
B)
Add them all together for the total area (A):
A = 140 + 56 + 4 + 20 + 12 = 140+60+32
= 232 sq.ft.
Hope that explains it well enough! ;)
Answer:
1/2
Step-by-step explanation: